Innovation, Hotel Industry and Megatrends: an introductory study - Medaglia, Juliana (2021)
Tourism, as a socioeconomic phenomenon, influences and is influenced by the waves and tendencies of the contemporary society. This article’s scope is to discuss the concept of innovation inserted on tourism, presenting the megatrends introduced by the Copenhagen Institute for Future Studies (CIFS, 2018), applied in this context to examples in the hotel industry area. Furthermore, the methodology that made this possible was based on exploratory research through systematic bibliographic review on tourism and knowledge management ibero-american databases, followed by documental analisis, presenting hotelary as its target. The results point to a theoretical gap between megatrends, trends and tourism innovation, and also indicate that the most found megatrends in the hotel industry are Technological Development, Sustainability and Individualization.